Members of the Regulatory Lymphocyte Club in Common Variable Immunodeficiency - Gupta, Sudhir; Demirdag, Yesim; Gupta, Ankmalika Abha (Frontiers in Immunology, 2022)
Role of regulatory (CD4) T cells is well established in peripheral tolerance and in the pathogenesis of murine model and human autoimmune diseases. CD4 Tegs have been investigated in common variable immunodeficiency (CVID). Recently, additional members have been added to the club of regulatory lymphocytes. These include CD8 Treg, Breg, and T follicular helper regulatory (TFR) cells. There are accumulating data to suggest their roles in both human and experimental models of autoimmune disease. Their phenotypic characterization and mechanisms of immunoregulation is evolving. Patients with CVID may present or are associated with an increased frequency of autoimmunity and autoimmune diseases. In this review, we have primarily focused on the characteristics of CD4 Tregs and new players of regulatory club and their changes in patients with CVID in relation to autoimmunity and emphasized the complexity of interplay among various regulatory lymphocytes. We suggest future careful investigations in large cohort of phenotypic and genotypically defined CVID patients to define their role in the pathogenesis of CVID and autoimmunity associated with CVID